Domains of common mental disorders in women reporting intimate partner violence - Ariane Gomes dos Santos; Claudete Ferreira de Souza Monteiro (Universidade de São Paulo, 2018)
Objective to verify associations between the types of intimate partner violence and the domains of common mental disorders in women. Method cross-sectional study with 369 women. The information was obtained through the instruments Self-Reporting Questionnaire and Conflict Tactic Scales. To analyze the data, Pearson's Chi-Square test, Fisher's exact test and Odds Ratio were used. Results women who reported physical abuse with and without sequela were respectively 2.58 and 3.7 times more likely to have symptoms of anxious depressed mood. The chances of experiencing symptoms of decreased vital energy increased by 2.27 times with psychological aggression, 3.06 times with physical abuse without sequelae and 3.13 times with physical abuse with sequelae. Somatic symptoms did not show statistical association with the types of violence. The propensity to develop symptoms of depressive thoughts increased 3.11 times with psychological aggression, 6.13 times with physical aggression without sequelae, 2.47 times with sexual coercion and 7.3 times with physical aggression with sequelae. Conclusion the types of intimate partner violence are strongly associated with the domains of common mental disorders in women. This finding may contribute to more accurate interventions by health professionals to women victims of violence.